Abdominal Injury at Mbarara Regional Referral Hospital, Uganda - Ruhinda, G.; Kyamanywa, P.; Kitya, D.; Bajunirwe, F. (East and Central African Journal of Surgery, 2008)
Background: Trauma poses a major public health challenge in Africa. This study was aimed at determining the prevalence, patterns and predisposing factors of abdominal injury in Mbarara Regional Referral Hospital (MRRH). Methods: A standard questionnaire was used to record the patterns, type and predisposing factors of injuries. All patients admitted to Mbarara Regional Referral Hospital (MRRH) with a diagnosis of abdominal injury over the study period made the study population. Results: Abdominal trauma accounted for 14.23% of the 836 trauma admissions seen over the study period. Fifty-two percent of the injuries had been sustained on the road. Males were five times more than females and the age range was 3-88 years, with a mode of 27 years. Blunt trauma accounted for 85.71% of abdominal injury, the spleen was injured in 43.7% and fractures were associated in 27.7%. Most patients (68.9 %) were managed nonoperatively. Conclusion: Blunt abdominal injury was the commonest pattern of injury (85.7%). Abdominal trauma is a common emergency at Mbarara Regional Referral Hospital accounting for 14.23% of admissions due to injury. Most injuries are a result of road traffic crushes (47.1%) and assault. Alcohol consumption is a major predisposing factor. Peasants are more predisposed to abdominal injuries. Non-operative management of hemoperitoneum is safe in hemodynamically stable patients.
Keywords: Abdominal; Injury; Hospital; Uganda